2021
DOI: 10.1016/j.ijinfomgt.2020.102212
|View full text |Cite
|
Sign up to set email alerts
|

Bring Your Own Device (BYOD) as reversed IT adoption: Insights into managers’ coping strategies

Abstract: Highlights This research explores the managers’ adaptation strategies resulting from BYOD usage by employees. The authors operationalize and enrich the coping model of user adaptation (CMUA). This research sheds light on the decisional processes in the adoption of coping strategies. The impact of the CMUA constructs varies according to the pre- or post-implementation period. This work helps managers for maximizing BYOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 139 publications
(246 reference statements)
0
15
0
1
Order By: Relevance
“…The results of the Harman one-factor test showed that the total variance was less than 50%, indicating that CMB was not a concern in this study (Podsakoff et al, 2003). Furthermore, the path coefficients and correlation of the constructs obtained from the structural model assessment had varying degrees of significance (Barlette et al, 2021;Williams, 2021). These results suggested that CMB was not a problem in data.…”
Section: Common Methods Biasmentioning
confidence: 62%
See 1 more Smart Citation
“…The results of the Harman one-factor test showed that the total variance was less than 50%, indicating that CMB was not a concern in this study (Podsakoff et al, 2003). Furthermore, the path coefficients and correlation of the constructs obtained from the structural model assessment had varying degrees of significance (Barlette et al, 2021;Williams, 2021). These results suggested that CMB was not a problem in data.…”
Section: Common Methods Biasmentioning
confidence: 62%
“…This study implemented some methods to assess and mitigate the influence of common method bias (CMB), as recommended by Barlette et al (2021). A priori procedural remedy by Podsakoff et al (2012) was included.…”
Section: Common Methods Biasmentioning
confidence: 99%
“…The study findings may be vulnerable to common method bias (CMB), as survey data were self-reported, and behavior was not quantified as it was based on users' self-assessment ( 124 ). As a result, some methods were implemented to evaluate and mitigate the potential for CMB, as recommended by ( 125 ). To be specific ( 126 ), priori procedural remedies were incorporated.…”
Section: Methodsmentioning
confidence: 99%
“…It can be accessed everywhere and anytime. Some researchers have investigated the effect of BYOD on both companies and academics (Barlette, Jaouen, & Baillette, 2021;Disterer & Kleiner, 2013). Their investigation stated the term or slogan BYOD gives a better contribution to their institution due to reduced operational costs.…”
Section: Implementing Bring Your Own Device (Byod)mentioning
confidence: 99%